The formation of future doctor’s language culture when studying medical terminology (practical material) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
The issues of language culture in the sphere of medical terminology are analyzed in the given article. There are presented the meaning of this section for future specialists and practical materials used by the author in teaching Ukrainian language course (for professional purposes) when studying lexical rules.
Keywords: language culture; lexical norm; medical terminology; practical task